(untitled) (Research, Society and Development, 2021)
The study of the anatomy discipline requires from the student a high capacity for attention and maintenance of concentration to achieve learning in its entirety, making it a laborious and exhausting process due to its intricate wealth of details. This fact corroborates the dispersion of student attention and the tiring effort of the teacher in trying to hold their attention during the teaching-learning process. Thus, technological tools aim to expand the possibilities of pedagogical practices contributing to greater student involvement by attributing the autonomy of the learning process. Nowadays, new technologies are implemented as helpers in the classroom, as they allow the enrichment of the content applied by the teacher to the students. This article aims to investigate the existence of scientific evidence related to the use of technology for teaching anatomy through active search in scientific research platforms. 180 scientific articles were found related to the selected keywords and arranged in analysis tables between the years 2008 to 2018, in English, Portuguese and Spanish. Of these, 9.4% articles were selected for full reading of their respective abstracts and this one; 41.17% were selected for full reading. The main themes found were the interference of technology in teaching the discipline of anatomy, the comparison between the traditional teaching method and the methodology associated with the use of virtual reality and simulation, and the motivation of students regarding the possibility of using new technologies in processes of teaching-learning. The results showed that there is strong evidence that the use of technological resources narrows the relationships of students and teachers, since the process becomes more playful and integrative while making the student autonomous from his own direction in the classroom, reducing the exhaustion inherent in studying the discipline in its traditional way.